SOSIALISASI BEASISWA STUDI LANJUT BERSAMA UPH, UNIMOR DAN IGI FLORES TIMUR - Pramusita, Santa Maya; Situmorang, Komilie; Arkianti, Maria Maxmilla Yoche; Lidya, Christie; Tahulending, Peggy; Siahaan, Desta Gloria; Pardosi, Lukas; Seda Mada, Grandianus (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Continuing education is one of the initiatives done to strengthen an institution's human resources. In Indonesia, there are various scholarship programs offered to people to continue their education. However, because many individuals have not been socialized, they are unaware of the scholarships that are accessible. To address this issue, the PkM team of Universitas Pelita Harapan, Universitas Timor, and the Flores Timor Teachers' Association collaborated to organize a socialization of scholarship for further education to the general public, especially in Eastern Indonesia. This event is conducted in the form of an online webinar and is filled out by three speakers from each institution, all of whom have won scholarships. The webinar began with a presentation session in which the presenters discussed their experiences and suggestions, followed by a question and answer session for each speaker, and a closing. According to the assessment results, several participants were excited about pursuing their study overseas. This is evident in the numerous thoughts and queries given by participants about continued study abroad scholarships. Overall, the webinar went well, with participants expressing their satisfaction with the information and experiences offered by the presenters. The assessment form also stated that participants desired an advanced scholarship socialization webinar so that they could learn more about the many sorts of further study scholarships they may apply for.